XX Balcanicum conference. Materials (22–23 X 2021): I. Osmańska groza nad Europą. Z dziejów walk zbrojnych z Imperium Osmańskim II. W stulecie sojuszu polsko-rumuńskiego. Rumunia i księstwa rumuńskie w polityce europejskiej - Sajkowski, Wojciech (Balcanica Posnaniensia. Acta et studia, 2021)
On October 22-23, 2021 the XX Balcanicum conference was held, organized by the Commission on Balkan Studies, in cooperation with the Faculty of History of Adam Mickiewicz University (UMU). At the conference, which was held in hybrid mode (stationary and remote), 21 papers were presented by researchers from Polish and foreign centers. The conference included two thematic sessions. The first one was entitled The Ottoman terror over Europe. From the history of military struggles against the Ottoman Empire. The choice of such a topic for the first session was connected with the fact that the year 2021 marks several round anniversaries of significant armed clashes with the Ottoman Empire. These begin with the Battle of Maritsa fought on September 28, 1371. , in which the Serbian army of King Vukašin and despot Jan Uglješa was defeated. Two hundred years later, in 1571, a fleet of allied Holy League states eliminated the Ottoman Empire from the ranks of the great naval powers at the Battle of Lepanto. Fifty years later in 1621, the Polish-Lithuanian army defended Chocim. The second thematic session that took place at the conference was entitled In the Centenary of the Polish-Romanian Alliance. Romania and the Romanian principalities in European politics. The choice of this topic was related to the fact that the second important anniversary falling in 2021 was the 100th anniversary of the Polish-Romanian alliance. This was the first alliance concluded by the reborn Polish state, functioned throughout the interwar period and resulted in the Romanian state accepting a huge number of Poles after the outbreak of World War II.